Experimental characterization and Monte Carlo simulations of the dose enhancement on the millimeter scale of PAGAT infused with gadolinium - Santibañez, M. (2021)
This study reports on the determination of the K-edge dose enhancement factor achieved in a polymer gel dosimeter based on acrylamide, known as PAGAT, infused with a high concentration of a clinical gadolinium-based compound. PAGAT dosimeters infused with gadolinium concentrations of 10 mg/mL and 20 mg/mL are characterized in terms of dose-response and sensitivity, obtaining the dose enhancement between two beam qualities for these Gd concentrations of clinical interest. Additionally, the dose enhancement ratio between these two concentrations was evaluated for each beam quality. To this aim, Gadodiamide solution, a Gd-based agent commonly used in clinics for magnetic resonance scanning, is used to manufacture Gd-infused dosimeters that are further irradiated with a 50 kVp X-ray beam in order to assess dose enhancement contributions exclusively from absorption from lower edges (L, M, etc.); subsequently, a 160 kVp spectrum optimized by yttrium and indium filtration is used to evaluate K-edge contributions. Gel dosimeter samples are prepared in spectrophotometric vials, and their readout is performed by optical density measurements, which is correlated with the absorbed dose. An appreciable increase was found in the K-edge dose enhancement factor (160kVp/50 kVp) for the samples with concentrations of 20 mg/mL and 10 mg/mL ranging from 1.20 to 1.61 and 1.10–1.41, respectively. These results could be interpreted as the contribution to the absorbed dose due the increment in the secondary radiation emitted from Gd atoms by K-edge interactions. Similarly, a relevant increase was observed in the dose enhancement when the Gd concentration is incremented from 10 mg/mL to 20 mg/mL obtaining factors of around 1.10–1.33 and 1.34–1.47 for the beam qualities 50 kVp and the optimized 160 kVp, respectively. Monte Carlo simulations using the PENELOPE main code are implemented aimed at complementing and comparing with the experimental results, showing differences of less than 4% for the K-edge dose enhancement factor and differences of less than 3% for the dose enhancement ratio for the studied beam qualities. In this regard, the results from the simulations support the reliability of the experimental measurements with this type of dosimeters within the studied concentration range. Finally, it is noticeable that the appreciable dose enhancement reported through this work was obtained infusing mass Gd as part of the Gadodiamide compound, already used as a contrast agent for magnetic resonance imaging, thus ensuring its suitability for clinical practices in humans.